A strategy for anode modification for future zinc-based battery application. Issue 11 (5th October 2022) - Zhou, Li-Feng; Du, Tao; Li, Jia-Yang; Wang, Yi-Song; Gong, He; Yang, Qiu-Ran; Chen, Hong; Luo, Wen-Bin; Wang, Jia-Zhao
Abstract : A critical review of zinc anodes and Zn metal-free anodes for future zinc-based battery application. Abstract : In the past several years, rechargeable zinc batteries, featuring the merits of low cost, environmental friendliness, easy manufacturing, and enhanced safety, have, attracted much attention. Zinc (Zn) anodes for zinc metal batteries play an important role. In this review, the fundamental understanding of these batteries and modification strategies to deal with the problematic issues for Zn anodes, including dendrite growth, corrosion, and the hydrogen evolution phenomenon will be summarized. The practical application of Zn anodes can still lead to Zn dendrites, various side reactions, and serious safety risks. Therefore, metal-free anodes for "rocking chair" zinc ion batteries to replace Zn anodes are systemically reviewed. The performance and the zinc storage mechanism of metal-free anodes will be discussed. Subsequently, a "rocking chair" zinc ion battery prototype selected as a recent example is assessed to explore the merits and demerits of Zn anodes and metal-free anodes. To conclude, a perspective on the future of zinc metal batteries and "rocking chair" zinc ion batteries is presented. It is hoped that this review may provide for further improvement of commercial rechargeable zinc batteries.